Pre-receptor regulation of 11-oxyandrogens differs between normal and cancerous endometrium and across endometrial cancer grades and molecular subtypes - Gjorgoska, Marija; Šturm, Lea; Lanišnik Rižner, Tea (Frontiers in Endocrinology, 2024)
Background: Endometrial cancer (EC) is a prevalent gynecological malignancy globally, with a rising incidence trend. While classic androgens have been implicated with EC risk, the role of their 11-oxygenated metabolites is poorly understood. Here, we studied 11-oxyandrogen formation from steroid precursors in EC for the first time.We performed in vitro studies on a panel of four EC cell lines of varying differentiation degree and molecular subtype and a control cell line of normal endometrium to assess 11-oxyandrogen formation from steroid precursors. We also characterized the transcriptomic effects of dihydrotestosterone (DHT) and 11-keto-DHT on Ishikawa and RL95-2. Key molecular players in 11-oxyandrogen metabolism and action were explored in endometrial tumors using public transcriptomic datasets.We discovered that within endometrial tumors, the formation of 11-oxyandrogens does not occur from classic androgen precursors. However, we observed distinct regulatory mechanisms at a pre-receptor level in normal endometrium compared to cancerous tissue, and between low-and high-grade tumors. Specifically, in vitro models of low-grade EC formed higher levels of bioactive 11-keto-testosterone from 11-oxyandrogen precursors compared to models of noncancerous endometrium and high-grade, TP53-mutated EC. Moreover, the potent androgen, DHT and its 11-keto homologue induced mild transcriptomic effects on androgen receptor (AR)-expressing EC model, Ishikawa. Finally, using public transcriptomic datasets, we found HSD11B2 and SRD5A2, coding for key enzymes in steroid metabolism, to be associated with better disease-specific survival, whereas higher intra-tumoral AR expression to correlate with lower recurrence in TP53-wt tumors.The intra-tumoral metabolism of 11-oxyandrogen precursors is characteristic for low-grade EC of non-TP53-alt molecular subtypes. Our findings support further exploration of circulating 11-oxyandrogens as prognostic biomarkers in EC.